(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Unemployment occurs when a person who is actively searching for employment is unable to find work OR the state of being without any work both for educated and uneducated person for earning one’s livelihood is meant by unemployment. Under the unemployment a person even being qualified and eligible for employment, but due to certain reasons found herself unemployed and this situation leads to a crisis. Unemployment is often used as a measure of the health of the economy. The most frequent measure of unemployment is the unemployment rate, which is the number of unemployed people divided by the number of people in the labor force. While the definition of unemployment is clear, economists divide unemployment into many different categories. The two broadest categories of unemployment are voluntary and involuntary unemployment. Voluntary unemployment is attributed to the individual’s decisions, whereas involuntary unemployment exists because of the socio- economic environment. These two broad categories of unemployment are further classified into three types, which are frictional unemployment, cyclical unemployment and structural unemployment. Therefore this study examines unemployment, its reasons and its social impact and consequences in Haryana.